Body size reference norms and subjective weight status: A gender and life course approach. (24th November 2017) - Wedow, Robbee; Masters, Ryan K; Mollborn, Stefanie; Schnabel, Landon; Boardman, Jason D
Abstract: This paper uses data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) to describe county-level variation in norms regarding physical weight among adolescents in the United States. We demonstrate that regardless of one's physical size, those residing in counties with a heavier weight norm are significantly less likely to see themselves as overweight than those residing in counties with a light weight norm. We further show that the local weight norm during adolescence (Wave 1) is associated with individuals' weight perceptions through adolescence and into young adulthood (Wave 4), though these associations attenuate in strength as respondents age. Our results suggest that weight norms have a stronger influence on weight perceptions among women compared to men, and that the role of gender is particularly important during adolescence. We encourage life course researchers to consider the normative health environment during adolescence as an important context for understanding disparities in health and health lifestyles as people age.